2006
DOI: 10.1371/journal.pgen.0020111
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Robustness Analysis of Cell Division Cycle Genes in Saccharomyces cerevisiae

Abstract: Intracellular biochemical parameters, such as the expression level of gene products, are considered to be optimized so that a biological system, including the parameters, works effectively. Those parameters should have some permissible range so that the systems have robustness against perturbations, such as noise in gene expression. However, little is known about the permissible range in real cells because there has been no experimental technique to test it. In this study, we developed a genetic screening meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
171
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(174 citation statements)
references
References 42 publications
3
171
0
Order By: Relevance
“…As a consequence, wild-type cells can cope with at least 10 extra copies of the SIC1 gene without significant slowing of growth rate (Thorntonand Toczyski 2003;Moriya et al 2006). This ability is dependent on Cln1 and Cln2, since cln1 cln2 cells are inviable with only a few extra copies of the SIC1 gene (Tyers 1996).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, wild-type cells can cope with at least 10 extra copies of the SIC1 gene without significant slowing of growth rate (Thorntonand Toczyski 2003;Moriya et al 2006). This ability is dependent on Cln1 and Cln2, since cln1 cln2 cells are inviable with only a few extra copies of the SIC1 gene (Tyers 1996).…”
Section: Discussionmentioning
confidence: 99%
“…We previously developed the genetic tug-of-war (gTOW) method to measure the limit of gene overexpression (Moriya et al 2006(Moriya et al , 2011(Moriya et al , 2012. Using gTOW, we can assess the limit of gene overexpression as the copy number limit (CNL) of the target gene as follows.…”
mentioning
confidence: 99%
“…In this study, we thus designated it on the basis of the overexpression limit measured by gTOW as the ''CNL of overexpression'' to distinguish the limit of protein overexpression. We previously determined the CNLs of cell cycle regulatory genes in the budding yeast and fission yeast and found that their CNLs were diverse, ranging from less than two to more than 100 (Moriya et al 2006(Moriya et al , 2011.…”
mentioning
confidence: 99%
“…10 Yeast cells, collected from 200 μL of saturated culture, were suspended in lysis solution (10 mM Na-phosphate (pH 7.5), 1.2 M sorbitol, and 2.5 mg/mL Zymolyase 100T) (Seikagaku, Tokyo, Japan) and incubated with a block incubator (BI-525, ASTEC, Fukuoka, Japan) for 10 min at 37 C to digest the cell wall. Then the cell suspension was heat-shocked at 94 C for Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9] Genetic screening by a genetic tug-of-war (gTOW) method allows the upper limit of each target gene in living cells to be measured by increasing the copy number of that gene. 10,11 Each target gene and its native regulatory DNA elements (promoter and terminator) are used as a unit so that the increased copy number of that gene can be determined quantitatively, and the gene expression level is expected to increase according to the copy number. Knowledge obtained from the gTOW method is important for understanding of biology at the system level.…”
Section: Introductionmentioning
confidence: 99%